ANALISIS KELAYAKAN FINANSIAL PENGOPERASIAN BUS TRANS METRO DEWATA DI KAWASAN METROPOLITAN SARBAGITA - Wijaya, I Komang Suta; Suthanaya, Putu Alit; Priyantha Wedagama, Dewa Made (JURNAL SPEKTRAN; Vol 13 No 1 (2025), 2025)
Population growth that continues to increase, increase in activities / activities, the need for movement from one place to another and the ease in the process of buying a vehicle are factors causing the increasing number of  private vehicle ownership. Meanwhile, the growth of roads is not commensurate with the growth in the number of vehicles and the role of public transport as an important component of transportation is getting worse from time to time. The government is here to fix public transportation services in the regions, one of which is the operation of the Trans Metro Dewata Bus in four corridors within the Sarbagita Agglomeration Area (Denpasar,  Badung, Gianyar and Tabanan). Trans Metro Dewata is one of the developments of road-based mass  transportation with a service purchase scheme. (buy the service) subsidized by the government. Based on these conditions, operators need to carefully plan their travel business. Operational costs, pricing of tariffs and  unexpected costs are further considerations for operators. For now, the amount of vehicle operating costs (BOK) and operating income obtained from the operation of the Trans Metro Dewata Bus are unknown. So this needs to get a more in-depth study, especially in financial feasibility. Based on the results of data processing with the assumption that the bus fleet from the government shows the total operational costs of Trans Metro  Dewata Bus vehicles from 2023 - 2029, which is IDR 282.256.543.602. Meanwhile, assuming the bus fleet from the operator, the total operational costs of Trans Metro Dewata Bus vehicles from 2023 - 2029 after  adding an initial investment cost of 25% of the capital, which is IDR 13,125,000,000 and as much as 75% of  IDR 39,375,000,000 in the form of a bank loan returned with installments with interest for 5 years, which is IDR 391.744.920.721. The operating income based on the buy the service scheme from 2023-2029 is IDR 366.173.491.600, while operating income based on the Tariff of Governor Regulation No. 112 of 2018 from  2023-2029 is IDR 67.495.948.574. Financially, the operation of the Trans Metro Dewata Bus with a service purchase scheme is feasible assuming the bus fleet is from the government, while assuming the bus fleet from  the operator operating the Trans Metro Dewata Bus is not financially feasible. Based on the tariff according to Governor Regulation No. 112 of 2018 the operation of the Trans Metro Dewata Bus is not financially feasible.